El aula invertida para el Aprendizaje de las Leyes de Newton en estudiantes de primero de Bachillerato General Unificado de la Unidad Educativa Cicalpa - Rojas Pomagualli, Jazmin Marianela (2024)
The aim of this research is to determine the incidence of using the flipped Classroom in the learning of Newton's Laws among first year students at the General Unified Baccalaureate of the Cicalpa Educational Unit. The research used a quantitative approach, since it was based on inferential statistics to analyze the data collected, the research design was quasi-experimental, characterized by deliberate manipulations of this type of design, the level of the research was explanatory since two variables were related, cause - effect. A non-probabilistic intentional sampling was carried out, that is to say in an intentional manner, where the sample consisted of students of A and B classes of first year of General Unified High School of the Cicalpa Educational Unit. It was determined that, with the application of the inverted classroom methodology, the students learned specific knowledge about the three Laws of (Newton, law of inertia, fundamental law of dynamics, law of action and reaction) and their applications, in this way the students of the experimental group (inverted classroom methodology) assimilated the information provided more quickly, unlike the students of the control group (traditional methods), which was complicated for them. Therefore, the implementation of flipped classroom methodology is recommended in order to evaluate more effectively the knowledge learned by the students.